Functional characterization of a novel plant growth-promoting rhizobacterium enhancing root growth and salt stress tolerance - Sanghee Lee; Young Kook Kim; Haulin Nie; Jongmin Ahn; Nayoung Kim; Seo-Rin Ko; Ah-Hyeon Choi; Hayoung Kwon; Yuxin Peng; Suk-Yoon Kwon; Ah-Young Shin (Scientific Reports)
Abstract Plant growth–promoting rhizobacteria (PGPR) are soil microorganisms through which phytohormones and other bioactive compounds are produced, thereby enhancing plant growth and stress tolerance. In this study, a novel PGPR strain was identified from the rhizosphere of Lycium chinense seedlings, which produce protein-rich fruit. Whole-genome sequencing and annotation revealed that the genome of this strain, designated Pseudomonas sp. A-2, consists of a 6.65-Mb circular chromosome with 5,980 predicted protein-coding sequences. Comparative genomic analysis classified the strain within the genus Pseudomonas. The A-2 strain genome encodes proteins involved in indole-3-acetic acid (IAA) biosynthesis and signaling pathways, which was validated through IAA detection assays and quantitative analyses. Plant growth rates were significantly enhanced by the A-2 strain treatment, with increases of 3-fold in Arabidopsis, 1.5-fold in tobacco, and 1.35-fold in peanut. In Arabidopsis thaliana, expression of key genes associated with lateral and adventitious root formation was induced by the A-2 strain treatment, including ARFs, AMI1, TAA1, YUCs, IBRs, TOB1, and ECH2. Moreover, enhanced tolerance to salt stress was conferred by the A-2 strain treatment, as evidenced by improved biomass accumulation, chlorophyll content, antioxidant enzyme activity, and reduced lipid peroxidation. Levels of total soluble sugars, including trehalose, were elevated in the A-2 strain treated plants, suggesting a role in osmotic adjustment under stress. The plant growth–promoting and stress-alleviating properties of Pseudomonas sp. A-2 highlight its potential application as an effective biological agent for sustainable agriculture.